2017
DOI: 10.3390/ijms19010027
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effect of Flavonoids and Chalcones: An Update

Abstract: Chalcones are precursors of flavonoid biosynthesis in plants. Both flavonoids and chalcones are intensively investigated because of a large spectrum of their biological activities. Among others, anticancer and antiangiogenic effects account for the research interest of these substances. Because of an essential role in cancer growth and metastasis, angiogenesis is considered to be a promising target for cancer treatment. Currently used antiangiogenic agents are either synthetic compounds or monoclonal antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 181 publications
3
64
0
2
Order By: Relevance
“…As it is shown in the Figure 10, significant decreases of VEGF protein and mRNA levels (10-20%) were observed only after MDA-MB-231 cells incubation with CUH and CUFH. Because VEGF stimulates membrane kinase receptor VEGFR2 following endothelial cells activation, diminished VEGF levels in the cellular environment and disruption of VEGF-related cell signaling may result in decreased proliferation, migration and tube formation [62]. In the case of MCF-7 cells, T. pratense phytocompounds showed almost a lack of influence in this field, yet still revealed chemoprevention of breast cancer cells.…”
Section: The Effect Of Trifolium Pratense L On Vegfmentioning
confidence: 99%
“…As it is shown in the Figure 10, significant decreases of VEGF protein and mRNA levels (10-20%) were observed only after MDA-MB-231 cells incubation with CUH and CUFH. Because VEGF stimulates membrane kinase receptor VEGFR2 following endothelial cells activation, diminished VEGF levels in the cellular environment and disruption of VEGF-related cell signaling may result in decreased proliferation, migration and tube formation [62]. In the case of MCF-7 cells, T. pratense phytocompounds showed almost a lack of influence in this field, yet still revealed chemoprevention of breast cancer cells.…”
Section: The Effect Of Trifolium Pratense L On Vegfmentioning
confidence: 99%
“…Administration of HESS did not show a protective effect in preventing an increase in serum VEGF concentration and a decrease in its soluble receptors, FLK-1 and sFLT-1 in diabetic rats. While HESS is rich in phenolic and avonoid compounds (93.3±1.5 mg GAE/g (DW) and 46 ± 1.7 mg QE /g (DW), respectively)(8), these ndings are inconsistent with the results of some studies that have stated that polyphenolic compounds downregulate the expression of angiogenic factors as an index of neovascularization (25,26). Park et al reported that polyphenols prevented the hypoxia-induced angiogenesis by reducing HIF-α transcriptional activity without altering its mRNA level, leading to reduce the expression of HIF-α downstream targets, including VEGF (27).…”
Section: Discussionmentioning
confidence: 97%
“…Materials and Methods. Structure-Structure, structure-plant family and structure-activity trends were analyzed from 285 pharmacologically evaluated flavonoids belonging to different aglycone families and originated from different plant taxa (Mirossay et al, 2018;Cirmi et al, 2016;Panche et al, 2016;Xiao, 2015;Lago et al, 2014;Kumar et Pandey, 2013;Semmar, 2010). Nonparametric comparison and link tests as well as multivariate analyses were applied to highlight/detect such trends (Semmar, 2011(Semmar, , 2013.…”
Section: Acylmentioning
confidence: 99%